pANALISIS SELISIH LABA KOTOR ATAS PENJUALAN BENUR PADA PT. CENTRAL PERTIWI BAHARI DI LAMPUNG SELATAN - Rudy - (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2010)
One way to analyze financial statements are the gross profit. Analysis of grossprofit is one facet of the analysis of the income or loss. This analysis is also important formanagement because of the comparison between realization of gross profit with a budgetor standard is needed.Where from this analysis can be known if there are unexpected changes in grossprofit. Besides, the analysis of gross profit can be known result of weak activity of thecompany's operations, so that action can be used as the basis for corrective action isrequired.To increase or maintain profit profit, then management needs to analyze the resultsof company operations, which can be learned from the company's financial statements.From those statements, management can know the state of development of the company.